SNP Variety of UMOD Gene in Patients with Hypertension Disease in Hilla Province - Abes, Sabreen.M. (International Journal of Scientific Research in Biological Sciences, 2025)
A major risk factor for cardiovascular illnesses, hypertension—also known as high blood pressure—is shaped by both environmental and hereditary elements. Recent research have shown several genetic variations linked to hypertension, among which the rs13333226 variant found in the Uromodulin gene (UMOD). This paper explores the biological relevance of Uromodulin, consequences of the rs13333226 variation, and possible function in hypertension. Fifty blood samples in all came from diabetic patients visiting the Diabetes Center at Merjan Teaching Hospital in Babylon, Iraq. Five samples in all were also gathered to act as a control group. PCR magnificues DNA taken from blood samples. The SOD2 gene was genotyped using a polymerase chain reaction (PCR) method then applying the DNA single-stranded conformation polymorphism (SSCP) method. The single-stranded conformation polymorphism (SSCP) technique thus verified the genuineness of these DNA polymorphisms. The findings show several haplotypes seen in SOD2. The findings showed that in the sick group the DNA polymorphism distribution was 84% and 16%; in the control group it was 70% and 30%. Understanding hypertension depends much on the rs13333226 variation on the Uromodulin gene. Clarifying the link between this variation and blood pressure control would help scientists open the path for better risk evaluation and focused treatments in the control of hypertension. Complete knowledge of the consequences of this variation and its possible influence in cardiovascular health depends on ongoing research.